2015
DOI: 10.1016/j.ydbio.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

ROBO2 restricts the nephrogenic field and regulates Wolffian duct–nephrogenic cord separation

Abstract: ROBO2 plays a key role in regulating ureteric bud (UB) formation in the embryo, with mutations in humans and mice leading to supernumerary kidneys. Previous studies have established that the number and position of UB outgrowths is determined by the domain of metanephric mesenchymal Gdnf expression, which is expanded anteriorly in Robo2 mouse mutants. To clarify how this phenotype arises, we used high-resolution 3D imaging to reveal an increase in the number of nephrogenic cord cells, leading to extension of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…In Slit2-or Robo2-deficient mice, ureteric bud formation fails to be restricted to a single site, leading to multilobular kidneys (Grieshammer et al, 2004;Yu et al, 2004), resembling the defects observed in human patients carrying mutations in ROBO2 (Lu et al, 2007). Robo2 is also important for the separation of the nephrogenic cord from the Wolffian duct, which prevents hyperproliferation of the cord (Wainwright et al, 2015). Even after development, Robo2 is necessary for podocyte stability in the mouse kidney by inhibiting nephrin-induced actin polymerization in podocyte feet via its binding partner Nck (Fan et al, 2012).…”
Section: Slit-robo Signaling In Organogenesismentioning
confidence: 94%
“…In Slit2-or Robo2-deficient mice, ureteric bud formation fails to be restricted to a single site, leading to multilobular kidneys (Grieshammer et al, 2004;Yu et al, 2004), resembling the defects observed in human patients carrying mutations in ROBO2 (Lu et al, 2007). Robo2 is also important for the separation of the nephrogenic cord from the Wolffian duct, which prevents hyperproliferation of the cord (Wainwright et al, 2015). Even after development, Robo2 is necessary for podocyte stability in the mouse kidney by inhibiting nephrin-induced actin polymerization in podocyte feet via its binding partner Nck (Fan et al, 2012).…”
Section: Slit-robo Signaling In Organogenesismentioning
confidence: 94%
“…Kidneys with duplex ureters are prone to blockage-related kidney damage with a subsequent loss of kidney function. Factors constraining the outgrowth process act by either limiting the domain of Gdnf expression within the intermediate mesoderm (Slit2/Robo2; Foxc1/Foxc2), or by inhibiting (Bmp4) or attenuating (Spry1) RTK pathway action within the ureteric bud (Grieshammer et al, 2004; Kume et al, 2000; Michos et al, 2004; Wainwright et al, 2015). Importantly, ureteric branching is rescued in Ret/Gdnf mutants when Spry1 action is also removed: branching now becomes highly dependent upon cap mesenchyme-derived Fgf10 signaling (Michos et al, 2010).…”
Section: From Progenitors To Products: Assembling the Kidneymentioning
confidence: 99%
“…Quantifying multiple cellular metrics within the developing mouse kidney has provided a broad overview of these events (Short et al, 2014; Combes et al, 2014). The size of the starting nephron progenitor pool at e10.5 is unclear, but a recent analysis has suggested around 2,000 cells (Wainwright et al, 2015). Extrapolating using cell cycle estimates from later stages with numbers determined at e11.5 by cell sorting (12,000 progenitors; Kobayashi et al, 2008) and confocal imaging (8,000 progenitors, A. Combes and M. Little, personal communication) gives a somewhat larger initiating population of 4,000 to 6,800 (A. Combes and M. Little, personal communication).…”
Section: From Progenitors To Products: Assembling the Kidneymentioning
confidence: 99%
“…Mouse models indicate that Slit-Robo signaling likely restricts interactions between the nephrogenic mesenchyme and ureteric bud to facilitate bud outgrowth at a single site [116,117]. Tenascin XB is an extracellular matrix glycoprotein that is expressed by uroepithelia of the UVJ, and thus may contribute to closure of the UVJ during voiding [115].…”
Section: Genetic Defects Leading To Cakutmentioning
confidence: 99%